PENGEMBANGAN BUKU ELEKTRONIK UNTUK SAINS DI SMP SBI DAN RSBI - Rochintaniawati, Diana; Widodo, Ari; Widhiyanti, Tuszie (Jurnal Pendidikan, 2012)
Research and development (R & D) of electronic books (e-book) for science in International Secondary Schools (RSBI and SBI) were conducted with the objective of providing science e-books as a source of learning for teachers and students of RSBI and SBI. With the development of this e-book, it was expected to develop an integrated understanding of science in students, develop students' language skills, and to develop skills in using information technology. The study was conducted by the method of R & D that begins with an analysis of national science curriculum and Cambridge curriculum. The e-book was presented in the form of integrated themes that combined concepts of physics, chemistry and biology written in English. From the results of feasibility study conducted on the use of the e-books it was found that the e-books were sufficiently met the criteria in terms of image presentation, animation, font used, English, exercises and student activities. In general, it was concluded that the e-book developed was creatively made and appropriate for learning source in secondary schools, particularly in RSBI and SBI. Penelitian Pengembangan Buku Elektronik untuk Sains di SMP SBI dan RSBI dilakukan dengan tujuan untuk menyediakan buku sains yang dapat dijadikan sebagai salah satu sumber belajar bagi guru dan siswa SMP di RSBI/SBI. Dengan dikembangkannya buku ini, diharapkan pembelajaran sains dapat mengembangkan pemahaman sains siswa yang terintegrasi, mengembangkan kemampuan berbahasa siswa, serta mengembangkan kemampuan dalam menggunakan teknologi informasi. Penelitian dilakukan melalui metode Reseach and Development (R&D) yang diawali dengan analisis kurikulum sains SMP berdasarkan KTSP dan kurikulum Cambridge. Penyajian buku berupa tema-tema yang mengintegrasikan konsep-konsep dalam fisika, kimia dan biologi dengan menggunakan Bahasa Inggris sebagai bahasa pengantar. Dari hasil uji kelayakan penggunaan buku yang dilakukan terhadap siswa SMP diperoleh bahwa e-book yang disusun memenuhi kriteria penggunaan e-book dalam aspek penyajian gambar, animasi, penggunaan huruf, penggunaan Bahasa Inggris sebagai bahasa pengantar, latihan serta kegiatan siswa. Secara umum, e-book yang dikembangkan dinilai memiliki kreativitas yang baik dan layak digunakan sebagai buku sumber dalam pembelajaran sains di SMP, khususnya di RSBI/SBI.